Pediatric Status Epilepticus: A Systematic Review of Clinical ‎Pattern, Challenges, and Outcomes - Shinde , Dr. Anwita Ramdas; Salunkhe , Dr. Shradha; Mane , Dr. Shailaja (International Journal of Basic and Applied Sciences, 2025)
Background:‎ Pediatric status epilepticus (SE) is a neurological emergency with substantial risk of death and ‎long-term disability. Clinical patterns and outcomes vary widely across regions, particularly ‎where delayed treatment and limited EEG or ICU access persist, necessitating a consolidated ‎appraisal to inform standardized care.‎Methods: ‎A PRISMA-guided systematic review of pediatric SE (ages 1 month–18 years) was conducted. ‎Twenty studies met the inclusion criteria for quantitative synthesis (n = 2,910). Data were extracted for ‎demographics, seizure types, etiologies, treatment, complications, and outcomes. For pooled ‎outcomes (mortality, refractoriness, sequelae), random-effects models with Freeman–Tukey ‎transformation were applied, reporting 95 % CIs and heterogeneity (I², τ²). Subgroup analyses ‎compared India vs non-India studies, acute symptomatic vs other etiologies, and refractory vs ‎non-refractory cases.‎Results: ‎Males comprised 56.7 %; generalized convulsive SE predominated (72.1 %). Acute ‎symptomatic causes (CNS infections, metabolic, hypoxic–ischemic injury) represented 54.3 %, ‎febrile SE 24.3 %. Refractory SE occurred in 26.1 %, super-refractory 3.3 %. Benzodiazepines ‎were the main first-line drugs; escalation commonly involved phenytoin/fosphenytoin, ‎levetiracetam, or valproate, with anesthetic infusions for RSE/SRSE. Pooled mortality ‎approximated 14–15 %, showing high inter-study heterogeneity due to differences in ‎prehospital delay, etiology mix, and ICU availability. Neurological sequelae affected 22–23 % ‎of survivors.‎Conclusions: ‎Pediatric SE remains a high-stakes emergency. Early benzodiazepine use, rapid escalation, and ‎standardized stepwise protocols are essential. Marked heterogeneity in mortality highlights the ‎need for prehospital training, faster treatment times, and expanded EEG/ICU capacity. ‎Prospective cohorts with uniform outcome metrics and exploration of immunotherapy in ‎NORSE are urgently needed‎.
Keywords: Pediatric Status Epilepticus; Refractory SE; NORSE; Acute Symptomatic; Levetiracetam; ‎Phenytoin; Systematic Review; Outcomes